"Against all odds" Does awareness of the risk of failure matter for educational choices?. (April 2022) - Cattaneo, Maria A.; Wolter, Stefan C.
Abstract: Educational decisions are always made under uncertainty. This paper examines the effect of providing information about dropout risks on stated preferences for academic versus vocational education in Switzerland, making use of the fact that there are marked historical and cultural differences in preferences for and enrolment rates in academic vs. vocational education across the different language regions. Since there is some harmonisation in terms of the required cognitive performance for an academic degree, different enrolment rates in academic education need to be partially corrected later, resulting in higher risks of dropout during the program in regions with higher preferences for academic education. By means of a survey experiment, we show that in those language regions with a strong preference for academic education, the disclosure of the risk of dropping out of education has no effect on preferences, while in the regions with less strong preferences for academic education, the information treatment on the risks significantly shifts preferences towards vocational education. Our results suggest that the deterrent effect of a higher risk of dropping out is too small to achieve an efficient allocation of talents, if preferences for a particular type of education are very strong.